Financial Safety Nets and Bank Resolution Frameworks in Southern Africa : Key Issues and Challenges - World Bank Group (Washington, DC: World Bank, 2019)
This report provides an assessment of the current state of development of financial safety nets and bank resolution frameworks in eight countries in southern Africa (Botswana, Eswatini [formerly Swaziland], Lesotho, Mozambique, Namibia, South Africa, Zambia, and Zimbabwe). It has been prepared to inform ongoing and planned technical assistance projects in the southern Africa region and to provide a basis for engagement with the authorities in each of the countries covered by the study. This summary draws from more detailed material contained in a comprehensive study.